A new cost effective algorithm for online identification of line outage contingency using current phasor of PMU. (September 2020) - Alam, Mehebub; Kundu, Shubhrajyoti; Thakur, Siddhartha Sankar; Banerjee, Sumit
Abstract: In this study, a new algorithm has been developed for online identification of line outage contingencies. The proposed algorithm is based on two novel parameters i.e., generator bus current deviation index (GBCDI) and line current distribution factor (LCDF). The proposed GBCDI is used to select the principal bus (PB), and therefore a line is selected named as principal line (PL), which is connected with the PB. The proposed LCDF for different contingency cases can be easily calculated and available to the power system operators. Now, the current through PL is monitored, and the PMU provided observed current through the PL is compared with calculated line current using LCDF for different contingency cases via the proposed objective function. Furthermore, PMU error is also incorporated in the objective function to make the developed model realistic. Moreover, for the proposed scheme, the PMUs are required to be placed at generator buses only, and this ensures cost-competitiveness over several existing methods. Additionally, parallel line outage modeling is also demonstrated which reveals the ability of the proposed scheme to identify the outage of parallel line. The proposed technique is applied on IEEE 6 bus, 14 bus, 57 bus, 118 bus systems, and the test results are compared with existing literature. Test results show the superiority of the proposed approach over several existing schemes in terms of identification accuracy and cost-effectiveness.